IMPACT OF ANESTHETIC MANAGEMENT ON TREATMENT OUTCOMES IN PATIENTS AFTER ESOPHAGECTOMY WITH SIMULTANEOUS PLASTICS WITHIN EXPRESS REHABILITATION PROTOCOL - V. A. Sizov; M. B. Raevskaya; A. E. Bukarev; S. A. Kamnev; D. V. Ruchkin; V. V. Subbotin (Вестник анестезиологии и реаниматологии, 2017)
Anesthetic management in extirpation of the esophagus with simultaneous plastic reconstruction has a direct control over the response to the treatment. Anesthesiologists are to be involved into all stages of treatment, starting from out-patient care. A team approach to treatment and development and introduction of the perioperative management protocol are required to achieve the best outcome. Multidisciplinary approach reduces the frequency of complications and time required for the follow-up post-surgical care.